Metodología para la formación en el arte del Aikido - José Santos Nalda Albiac (Universidad de León, 2012)
Ishana Pérez Peña. Tenerife: Ishana Pérez Peña, 2007. 368 páginas. 15x24 cm. I.S.B.N.: 978-84-611-9652-4.